(untitled) (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2022)
: Education must be oriented to the competencies needed by the world of work because the percentage of unemployed among educated people continues to increase. This study aims to examine the level of relevance (suitability) and tightness in job competition for graduates of Islamic Economics at IAIN Pekalongan. The study is only directed at the type of work for Alumni 1 year and alumni 3 years ago. This study took the subject of the alumni of the Islamic Economics Study Program. The sampling technique used is snowball sampling. The data collection technique used questionnaires and documentation, while the data analysis technique used descriptive analysis. This study found that the most dominant type of work for alumni 3 years ago was Labor and the most dominant type of work for the alumni of yesterday’s graduates was Entrepreneurship.